2018
DOI: 10.1152/ajprenal.00137.2018
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin attenuates kidney injury and fibrosis in deoxycorticosterone acetate-salt and angiotensin II-induced CKD mice

Abstract: Adiponectin (ApN) is a multifunctional adipokine. However, high, rather than low, concentrations of ApN are unexpectedly found in patients with chronic kidney disease (CKD) via an as yet unknown mechanism, and the role of ApN in CKD is unclear. Herein, we investigated the effect of ApN overexpression on progressive renal injury resulting from deoxycorticosterone acetate-salt (DOCA) and angiotensin II (ANG II) infusion using a transgenic, inducible ApN-overexpressing mouse model. Three groups of mice [wild type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 53 publications
1
33
0
Order By: Relevance
“…They found that APN decreased the expression of PAI‐1, FN and α‐SMA in the renal cortex following induction by DOCA‐salt combined with angiotensin II (Ang II). APN also decreased the expression of proinflammatory factors (NF‐κB‐p65 and pERK1/2) and oxidative stress‐related factors (NOX2 and p47phox), ameliorated renal fibrosis, reduced podocyte damage and reduced overall inflammation and oxidative stress 20 . APN inhibits the production of the pro‐inflammatory factor IL‐8 in a dose‐dependent manner.…”
Section: Role Of Apn In Renal Fibrosismentioning
confidence: 88%
See 1 more Smart Citation
“…They found that APN decreased the expression of PAI‐1, FN and α‐SMA in the renal cortex following induction by DOCA‐salt combined with angiotensin II (Ang II). APN also decreased the expression of proinflammatory factors (NF‐κB‐p65 and pERK1/2) and oxidative stress‐related factors (NOX2 and p47phox), ameliorated renal fibrosis, reduced podocyte damage and reduced overall inflammation and oxidative stress 20 . APN inhibits the production of the pro‐inflammatory factor IL‐8 in a dose‐dependent manner.…”
Section: Role Of Apn In Renal Fibrosismentioning
confidence: 88%
“…They found that APN activated AMPK signalling pathways and thereby reduced Ang II‐mediated induction of PAI‐1, fibronectin (FN), α‐SMA and fibrosis indexes. APN therefore reduces the extent of renal fibrosis and damage of podocytes, and provides a renoprotective effect 20 …”
Section: Role Of Apn In Renal Fibrosismentioning
confidence: 99%
“…Interestingly, these anti-inflammatory actions also take place locally in the kidney, as adiponectin receptors are present in renal cells [ 29 ]. Moreover, Tian et al recently showed in rodents that adiponectin is a renoprotective agent that attenuates kidney injury and fibrosis [ 30 ]. Therefore, our results, pointing to a beneficial effect of the SNP (as it was associated with better graft function), would be in line with those reports linking the T-variant allele with increased adiponectin activity [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many in vivo experiments have confirmed the anti-fibrotic action of APN in the kidney. The mRNA expression and deoxycorticosterone acetate-salt 30 and Ang II infusion-induced production of these fibrotic markers in the renal cortex were reduced in wild type mice showing APN overexpression [25].…”
Section: Role Of Adiponectin In Anti-renal Fibrosismentioning
confidence: 93%
“…Clinically, conditions such as diabetic nephropathy, immunoglobulin A nephropathy (IgAN), and lupus nephritis (LN), which are associated with CKD can precipitate renal fibrosis [21,22]. In recent years, a large number of studies have investigated the role of APN in renal fibrosis associated with these diseases, and the consensus based on the available literature confirms the renoprotective effect of APN [23][24][25]. Clinical and basic research has characterized the significant physiological role of APN, and a strong association has been observed between serum APN levels and outcomes of various renal diseases [26].…”
Section: Role Of Adiponectin In Renal Fibrosismentioning
confidence: 99%